PENGARUH GAYA KEPEMIMPINAN, KOMITMEN ORGANISASIONAL DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA LEMBAGA PRESTASI INDONESIA DUNIA - Michael Eric Atin, 13.05.51.0141; Sungkowo Utomo, Budi (Students' Journal of Economic and Management, 2018)
This research is purposed to analyze the effect of Leadership styles, Organizational Commitment, and Work Stress on employee performance at Lembaga Prestasi Indonesia Dunia. The study took 81 employees as a sample from Lembaga Prestasi Indonesia Dunia. The data was analyzed by using multiple regression analysis. The Result of research indicate Leadership styles and Organizational Commitment have positive significant effect on employee performance. But, Work Stress have positive significant effect on employee performance at Lembaga Prestasi Indonesia Dunia.Keywords: Leadership style, Organizational Commitment, Work stress, Employee performance